ASSESSMENT OF THE PRESENCE OF SIMULIUM SPP BLACKFLIES AND ONCHOCERCIASIS IN SELECTED COMMUNITIES AROUND AWHUM WATERFALLS, A TOURIST SITE IN UDI LGA OF ENUGU STATE, NIGERIA (FUDMA JOURNAL OF SCIENCES, 2025)
The study is an assessment of the abundance of blackflies (Simulium spp.) and Onchocerciasis in selected communities around Awhum waterfalls, a tourist site in Udi LGA of Enugu State, Nigeria. For the entomological aspect of this work, traps were set to catch and collect black flies in and around the Awhum Monastery which does not only serve as a tourist site but also a religious pilgrimage ground. Serological screening using Standard diagnostics test kits for Onchocerciasis (SD-Bioline OV16 kits) was used to screen 125 participants, who were members of the communities ranging from ages 5 – 70 years and comprising of 50 males and 75 females. The result revealed that only 28 (22.4%) of the participants were positive while majority 97(77.60%) were negative. Nineteen (19) positive cases were confirmed by molecular analysis of mitochondrial cytochrome oxidase subunit I (COI) gene. Of the total positive cases, more males 16(57.1 4%) than females 12(42.86%) were infected with Oncocerca volvulus. The findings confirmed the presence of blackflies and the endemicity of Onchocerciasis (River Blindness) in communities around the Awhum waterfalls, a tourist site in Awhum, Udi Local Government Area of Enugu State.
Keywords: Onchocerciasis; Blackfly; Onchocerca volvulus; Awhum; Tourist